The social status of Muslim women in contemporary society: headscarf deadlock in Turkey as a case study - Demirel, Serdar (IIUM Press, 2009)
Introduction: Almost two-thirds of Turkish women wear a headscarf. This is a reality of Turkish society. But, the headscarf is banned in universities, public schools, Parliament, and among public servants and professionals. It is quite difficult to understand how....